Indigenous Cellulosic Raw Materials for the Production of Pulp, Paper and Board Part VII.-writing and Printing Papers from Phragmites karka, Trin. - Bhat, R. V.; Virmani, K. C. (Indian Forester, 1952)
Laboratory experiments on the production of chemical pulps by the soda and sulphate processes from Phragmites karka, Trin. ( nal ) are described. The results of pilot plant experiments on the production of chemical pulps and writing and printing papers are included. Since this species of grass grows in habitats where another similar species Arundo donax, Linn., is found, a digestion on a pilot plant scale of a mixture of these two grasses was carried out with satisfactory results. Samples of paper made from Phragmites karka and from the pulp obtained by digesting the mixture of this species and Arundo donax are inserted in this bulletin. The pulps from Phragmites karka are short-fibred and hence the admixture of these pulps with longfibred pulps such as those of sabai grass (Eulaliopsis binata) or bamboo is essential for the successful use of this reed for the production of paper on a commercial paper machine. It is reported that this species is found in large quantities in Assam. Since transportation of this reed-like grass to places outside Assam at an economic price is not possible, attention must be directed to the establishment of a paper mill in Assam utilizing this species. Bamboo is also available in Assam for the production of chemical pulp for admixing with the short-fibred pulp of Phragmites karka for the manufacture of paper.